2016
DOI: 10.1111/bju.13480
|View full text |Cite
|
Sign up to set email alerts
|

Posterior musculofascial reconstruction after radical prostatectomy: an updated systematic review and a meta‐analysis

Abstract: To evaluate the influence of posterior musculofascial plate reconstruction (PR) on early return of continence after radical prostatectomy (RP); an updated systematic review of the literature. A systematic review of the literature was performed in June 2015, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and searching Medline, Embase, Scopus and Web of Science databases. We searched the terms posterior reconstruction prostatectomy, double layer anastomosis pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 24 publications
3
43
0
2
Order By: Relevance
“…A systematic review by Rocco et al [39] concluded that this was due to the different continence definitions in each analyzed study, several modifications to the original surgical technique, and different surgical approaches. Grasso et al [40] performed a meta-analysis of available studies and concluded that an overall statistically significant advantage in the rate of postoperative UC in favor of posterior reconstruction at 3–7 days after catheter removal (RR 1.90, 95% CI 1:25–2:90; p  = 0.003), at 30 days after catheter removal (RR 1.77, 95% CI 1.43–2.20; p  < 0.001), and at 90 days after catheter removal (RR 1.32, 95% CI 1.10–1.59; p  = 0.003) was found supporting its incorporation into clinical practice.…”
Section: Surgical Techniques To Optimize Urinary Continencementioning
confidence: 99%
“…A systematic review by Rocco et al [39] concluded that this was due to the different continence definitions in each analyzed study, several modifications to the original surgical technique, and different surgical approaches. Grasso et al [40] performed a meta-analysis of available studies and concluded that an overall statistically significant advantage in the rate of postoperative UC in favor of posterior reconstruction at 3–7 days after catheter removal (RR 1.90, 95% CI 1:25–2:90; p  = 0.003), at 30 days after catheter removal (RR 1.77, 95% CI 1.43–2.20; p  < 0.001), and at 90 days after catheter removal (RR 1.32, 95% CI 1.10–1.59; p  = 0.003) was found supporting its incorporation into clinical practice.…”
Section: Surgical Techniques To Optimize Urinary Continencementioning
confidence: 99%
“…In their systematic review and meta-analysis, Grasso et al [1] address the question of whether posterior muscolofascial reconstruction (PMR), the so-called Rocco stitch, positively affects urinary continence after radical prostatectomy. The relevance of the question to this structured form of inquiry is that individual studies to date have been inconclusive.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…It therefore seems logical to reserve re-TUR only for those patients who truly need it, so that limited resources are focused on ensuring that they receive their operation in a timely manner, ideally within 2-4 weeks. If adopted into day-to-day urological practice, the findings by Gontero et al [1] will allow many patients with HG/G3 T1 and detrusor muscle in the first TURBT specimen to avoid a re-TUR and start intravesical therapy without further delay. Pragmatically, the same should apply to patients with HG/ G3 Ta with detrusor muscle in the specimen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Anterior reconstruction (AR) was introduced by Tewari et al . 8 and later combined with PR to yield an incremental benefit (AR + PR) 911 . A simple anterior suspension (AS) technique using sutures anchored to the pubic bone was first described by Sugimura et al .…”
Section: Introductionmentioning
confidence: 99%